Metallothionein expression correlates with metastatic and proliferative potential in squamous cell carcinoma of the oesophagus - Hishikawa, Y (Nature Publishing Group, 1999)
The goal of this study is to clarify whether the expression of metallothionein (MT) could affect the prognosis and the metastatic potential of squamous cell carcinoma (SCC) of the oesophagus. In paraffin-embedded specimens resected from 57 patients, MT mRNA and protein expressions were detected by in situ hybridization and immunohistochemistry respectively. The expression of MT was evaluated in respect of clinicopathologic variables and patients' survival. MT mRNA expression was significantly associated with the proportion of lymph node metastasis (71% in MT mRNA-positive tumours vs 42% in MT mRNA-negative tumours; P = 0.0343) and that of distant metastasis (29% in MT mRNA-positive tumours vs 5% in MT mRNA-negative tumours; P = 0.0452). In respect of MT protein expression, the frequency of distant metastasis was more common in MT-positive tumours than in MT-negative tumours (30% in MT-positive tumours vs 8% in MT-negative tumours; P = 0.0446). The survival rate of the patients with MT protein-negative tumours was significantly better than that of the patients with MT protein-positive tumours (P = 0.0340). There was a positive correlation between the expression of MT protein and that of proliferating cell nuclear antigen (P = 0.0018). Therefore, we conclude that MT expression, both at the mRNA and protein levels, may be a potential marker predicting metastatic and proliferative activities of oesophageal SCC. © 1999 Cancer Research Campaign